Analisis Perkembangan Film Komedi Indonesia - Rizky Hafiz Chaniago (Nyimak: Journal of Communication, 2018)
Dalam sejarah perfilman Indonesia, film komedi mulai muncul pada dasawarsa 1950-an, bersamaan dengan diproduksinya film nasional pertama yang disutradarai Nya’ Abbas Akup. Film komedi Indonesia paling banyak diproduksi pada 1980-an dan sebagian besar dibintangi oleh grup yang menamai dirinya Warkop DKI. Dalam perkembangannya, film komedi di era 2000-an terbagi menjadi beberapa genre. Tulisan ini memaparkan sejarah perkembangan film komedi di Indonesia dalam tiga periode: era klasik (1960- 1970), era pertengahan (1980-1990) dan era milenium (2000-hingga kini).Kata Kunci: Perfilman Indonesia, komedi, sejarah film komedi Indonesia In the history of Indonesian cinema, comedy films began appearing in the 1950s, along with the production of the first national film directed by Nya' Abbas Akup. Indonesian comedy films were mostly produced in the 1980s and mostly starred by a group calling itself Warkop DKI. In its development, comedy films in the 2000s were divided into several genres. This paper describes the history of the development of comedy films in Indonesia in three periods: classical era (1960-1970), middle era (1980-1990) and millennium era (2000-up to present).Keywords: Indonesian movie, comedy, history of Indonesian comedy